In vitro investigations of coelomic fluid of Eisenia fetida: protein analysis, antioxidant activities and antibacterial effects on diabetic wounds' bacteria - Negar Danafar; Marzieh Shokoohi (Iranian Journal of Microbiology)
Background and Objectives: Diabetes is a metabolic disorder characterized by elevated glucose levels, leading to complications such as infections and impaired wound healing. Diabetic wounds are prone to bacterial infections, with common pathogens including Staphylococcus, Escherichia coli, Bacillus subtilis and Pseudomonas aeruginosa. Coelomic fluid of Eisenia fetida (CFEF) exhibits antimicrobial properties, making it a potential alternative to traditional antibiotics. This study aims to evaluate the in vitro antibacterial effects of CFEF on diabetic wound pathogens, alongside analyzing its protein content and antioxidant activities. Materials and Methods: This study used bacterial strains Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Bacillus subtilis ATCC 19659, and Pseudomonas aeruginosa ATCC 27853. CFEF was extracted using warm water and electric shock methods. Protein concentration was determined using the Bradford method, and protein analysis was conducted via Tricine SDS-PAGE. Antioxidant activities were evaluated using DPPH, FRAP, superoxide dismutase, and catalase assays. Antibacterial activities were tested by disc diffusion, MIC, and MBC methods. Results: The study showed that CFEF exhibited significant antibacterial and antioxidant activities against common bacteria found in diabetic wound infections. The warm water shock method yielded superior results compared to the electric shock method. Conclusion: CFEF demonstrates promising antibacterial and antioxidant properties, suggesting its potential as a natural alternative for treating diabetic wound infections. Further research is needed to evaluate its clinical application and safety.